Limb salvage procedure in immunocompromised patients with therapy‐resistant leg ulcers—The value of ultra‐radical debridement and instillation negative‐pressure wound therapy - Geierlehner, Alexander (Int Wound J, 2020)
The purpose of this study was to analyse the outcome of our established triple treatment strategy in therapy‐resistant deep‐thickness chronic lower leg ulcers. This limb salvage approach consists of ultra‐radical surgical debridement, negative‐pressure wound therapy (NPWT) with or without instillation, and split‐thickness skin grafting. Between March 2003 and December 2019, a total of 16 patients and 24 severe cases of lower leg ulcers were eligible for inclusion in this highly selective population. A total of seven patients received immunosuppressive medication. Complete wound closure was achieved in 25% and almost 90% of included lower leg ulcer cases after 3 and 24 months of our triple treatment strategy, respectively. The overall limb salvage rate was 100%. Bacterial colonisation of these wounds was significantly reduced after multiple surgical debridements and NPWT. Fasciotomy and radical removal of devitalised tissue such as deep fascia, tendons, and muscles combined with NPWT showed promising results in terms of the overall graft take rate. This treatment strategy was considered as last resort for limb salvage in such a critically ill and immunocompromised patient population. Surgeons should be aware of its efficacy and consider the triple treatment strategy especially if no other limb salvage option remains.